Blurred Lines: Public School Reforms and the Privatization of Public Education - Erika K. Wilson (Washington University Journal of Law & Policy, 2016)
This Article discusses the shift in education reform from judicially-based efforts concerning public school improvement for minority and poor students to market-based reform concerning individual access to improvement opportunities. Wilson highlights the significance of this shift by drawing attention to the judiciary’s diminishing role in education regulation and to structural changes in how the role of public education is conceptualized. Wilson argues that market-based school reform diminishes public education’s ability to bring positive externalities by focusing on individual improvement and failing to address systemic issues in our public education system.
Keywords: Public School; Reform; Privatization; Public Education; Desegregation; School Finance Litigation; Vouchers; Charter Schools; Quality Public Education; minority students; poor students; Urban areas